Język - Wisser, Richard (Wydawnictwo Naukowe Instytutu Filozofii UAM, 2012)
What is the difference between language and chatter of today? The genuine language (of yesterday) has the power „to create the endless worlds, to give names of God and mans, to show the depth of human emotions”. Nowadays can language „only inform and multiply the words”. We should bring the former language back to life. One can interpret the following poems in the key of symbolic philosophy (constructivism) or in the key of romantic philosophy (universal communication).
Keywords: Language; Essence of language; Language against chatter